PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN SIKAP GOTONG ROYONG DAN PRESTASI BELAJAR PESERTA DIDIK MATERI PENGUKURAN LUAS DI KELAS IV A SD NEGERI MERTASINGA 07 - Safitri Dwi Anggraeni; Badarudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Engagement from students was low, with many students still selective in choosing friends in social settings and showing little interest in making new friends. The low academic achievement of the students, largely due to their lack of focus in class and their perception of math as an uneasy and boring subject, provided additional context for the research. In view of this, a two-cycle phased classroom action research project with two meetings was conducted. Each cycle included planning, implementation, observation, and reflection. Grade IV students of SD Negeri Mertasinga 07 became the subject of this study, which aimed to improve their math learning and gotong royong attitude. Data was collected using questionnaires, assessment sheets, and observation sheets. The results showed that gotong royong improved in both cycles. During cycle II, the mean score of cooperative attitude increased from 2.18 in cycle I to 2.84. Students' math learning achievement increased in each cycle. The learning achievement level in the first cycle was 55.17% (or an average of 69.13 points), while in the second cycle it reached 94.82% (or an average of 84.65 points). The increase in academic achievement was 39.65 percent.